Występowanie gadów na terenie Leśnego Zakładu Doświadczalnego SGGW w Rogowie - Gryz, Jakub; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2022)
The aim of this study was to inventory the reptile fauna in the area of the Experimental Forest Station of Warsaw University of Life Sciences in Rogów. The study area encompassed 225 km2 of field and forest mosaic and all reptiles observed during fieldwork in the years 2011–2021 were recorded. Additionally, historical records were analysed and the diet of avian as well as mammalian predators inhabiting the study area were reviewed. During field studies, five different native species were recorded: slow worm Anguis fragilis , sand lizard Lacerta agilis , viviparous lizard Zootoca vivipara , grass snake Natrix natrix , common European adder Vipera berus . We also observed two alien species; pond slider Trachemys scripta and tortoise Testudo sp. Slow worms and grass snakes were the most common, while the diets of predators mostly contained unidentifiable lizards.